Implementation Of Land And Building Tax (PBB) Reduction Policy For Individual Taxpayers In Palembang City - Desi Novita Sari; M.Husni Thamrin; Akhmad Mustain (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Objective: This study aims to analyze the implementation of the Land and Building Tax (PBB) reduction policy for individual taxpayers in Palembang City based on the principles of Adam Smith's Canons of Taxation. Furthermore, this study aims to identify factors influencing the success of implementation and compare the realization of the policy across three recipient criteria: the underprivileged, retirees, and veterans. Method: This study used a qualitative descriptive method with a field study approach in Palembang City. Data were collected through direct observation, documentation, and in-depth interviews with eight key informants, including the Head of the Palembang City Regional Tax Management Agency (Bapenda), relevant technical officials, and taxpayer representatives from each category. Data analysis techniques included data condensation, data presentation, and drawing conclusions, the validity of which was tested through source triangulation. Results: The research findings indicate that the policy implementation has been quite successful, meeting four main aspects: (1) Equality, through factual verification of taxpayers' economic conditions and the provision of inclusive services for vulnerable groups; (2) Certainty, based on the legal basis of Mayoral Regulation No. 5 of 2020 and SOPs that guarantee a 7–14-day service time; (3) Convenience of Payment, through the provision of digital payment channels and e-commerce; and (4) Economic of Collections, which has successfully increased compliance and reduced tax arrears. However, there is a gap in implementation, with pensioner criteria dominating applications compared to veterans and low-income groups.Implications: The results of this study suggest the need for more extensive outreach, especially for veterans and low-income groups, to minimize information gaps. For policy practitioners, it is recommended to accelerate the transition to full digitalization to reduce reliance on physical documents and increase administrative efficiency. Future research could expand the scope to corporate taxpayers or analyze the effectiveness of policy communication at the grassroots level.